Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.bjoms.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal lesions in patients with COVID-19: a systematic review

Abstract: COVID-19 is a new disease which mainly presents with respiratory symptoms, however can present with a multitude of signs and symptoms affecting various body systems. Several oral manifestations related to COVID-19 have also been reported. We carried out a systematic review to explore the types of oral mucosal lesions that have been reported in COVID-19 related literature up to the date of 25th of March 2021. A structured electronic databases search using Medline, Embase and CINAHL as well as gray li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 23 publications
0
42
0
1
Order By: Relevance
“…The studies also identified ‘oral mucosal changes’ in a large number of the study population, however the specific changes were not mentioned and therefore cannot be compared to the rest of the data [ 11 ]. Two of the five studies included in this review were systematic reviews, the first reported on oral lesions in patients with COVID-19 [ 3 ] and the second one reported on PIMS-TS [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies also identified ‘oral mucosal changes’ in a large number of the study population, however the specific changes were not mentioned and therefore cannot be compared to the rest of the data [ 11 ]. Two of the five studies included in this review were systematic reviews, the first reported on oral lesions in patients with COVID-19 [ 3 ] and the second one reported on PIMS-TS [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of oral mucosal lesions in this paper were cheilitis in 32.6% and tongue swelling in 4.7% of the sample. Bhujel et al [ 3 ] reported on oral mucosal lesions in both adult and paediatric patients with SARS-CoV-2 infection. Of the 12 studies appraised in this systematic review, a total of 84 paediatric patients were reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations